Modelagem da Taxa de Retenção de Sedimentos (SDR) em uma bacia hidrográfica do semiárido brasileiro utilizando o modelo InVEST - Silva, Erika Roanna da (2024)
The soil erosion process, coupled with its intensity, contributes to a decline in water quality by increasing turbidity, reducing the concentration of dissolved oxygen and nutrients, as well as resulting in the loss of nutrients from the topsoil. Therefore, an assessment of hydrosedimentological behavior is essential for identifying potentially erosive areas and places where deposition processes predominate. Based on these premises, the hypothesis is that the InVEST model is capable of accurately quantifying and mapping variations in the erosion process using a simple parameterization, acting as an effective tool for environmental management and soil erosion prevention. Therefore, the general objective of this work is to spatially analyze the behavior of the sediment retention rate in the Seridó River basin, a semiarid region between the states of Rio Grande do Norte and Paraíba, based on the current land use and land cover scenario. To do this, the Sediment Delivery Ratio (SDR) module of the InVEST model was used and the data was then calibrated using Nash-Sutcliffe. According to the estimated results, the Erosivity values for the region varied between 2.208 and 4.802 MJ.mm. ha -¹. h -¹. year -¹, the erodibility (K factor) showed that some areas of the upper reaches of the rivers are more erodible, which causes greater sediment transport by the force of drainage incision. The slope analysis using the digital elevation model (SRTM) revealed that the average slope of the basin is 8%, classifying it as a region of undulating relief. The average estimate of sediment loss was 26,14 tons ha -¹. year -¹. for the entire basin, with 18% sediment retention at the basin outlet. It was noted that sediment retention is lower in areas associated with human activities (pastures and agriculture), while the contribution to sediment production is greater in these areas and where the soil is exposed. It can be seen that sediment retention prevents an average of 32.204.470 tons of soil loss from the watershed per year. It can be concluded that InVEST is capable of accurately spatializing and estimating erosion processes since it uses accessible input data that requires knowledge of geographic information systems.